The Concept of Dharuri Bisy Syaukah in Fikih Siyasah: A Study of the Thought of Abuya Muhammad Waly Al-Khalidi - Aulia Ababiel; Safriadi Safriadi (Siyasah Wa Qanuniyah, 2025)
During Soekarno's administration, several significant events took place, including the emergence of the DI/TI movement led by Sekarmadji Maridjan Kartosuwirjo. This movement, also known as DI/TII, operated under the Tentara Islam Indonesia (TII) and aimed to establish an Islamic State of Indonesia. Concurrently, Islamic parties debated not only the desired form of an Islamic state but also the legitimacy of President Soekarno as ulil amri (leader deserving of obedience) due to the government not being Islamic. Amidst ongoing debates within the Islamic factions in the Constituent Assembly, President Soekarno convened approximately 500 ulama from Java and two prominent ulama from Aceh, Teungku M. Hasan Krueng Kalee and Abuya Muda Wali al-Khalidy, at Istana Cipanas on October 14, 1957. They discussed the status of the Indonesian state and its president under Islamic jurisprudence, deliberating on whether his leadership was legitimate according to Islamic principles. Out of this meeting emerged the concept of "Waliyul Amri Dharuri Bisy Syaukah", bestowed upon President Soekarno, affirming his legitimacy as the head of state despite Indonesia not being an Islamic nation. The scholarly work discussed in this context employs library research as its method, gathering theoretical insights by studying relevant literature. The research findings underscore the proposal of "Dharuri Bisy Syaukah," a consensus reached among the attending ulama, which solidified President Soekarno's legitimacy as the national leader.